Study of the Hadith Regarding Fever in the Perspective of Ma’anil Hadith Yusuf Qardhawi - Nur Fadillah (Spiritus: Religious Studies and Education Journal, 2024)
The article discusses the hadith of the Prophet related to science, one of which is the hadith narrated by al-Bukhari where he mentions that the hadith of fever as a fragment of hellfire contained in the book of shahih al-Bukhari is not understood with its true meaning, but this hadith is understood with a new meaning that is majas and this hadith is included in the hadith isti'arah tamsiliyyah. This form of research is Library research Because this research is bibliographical, the data used is determined by two data sources: primary data and secondary data. Then to understand the hadith so that it can be understood clearly and more easily in the current context, the author uses the ma'anil hadith method offered by Yusuf al-Qardhawi in his book on the study of criticism as-sunnah. Distinguish the true expressions and majaz in understanding hadith, understanding hadith based on background, social conditions and goals, and understanding the meaning of word for word. The conclusion in the discussion of the hadith about fever as a fragment of hellfire is in accordance with the sound of his eyes that the Prophet gave a parable about the heat of fever just like the hellfire of God and the advice of the Prophet to relieve fever by using water. The wisdom of fever, when people have a fever, the levels of interferon substances in the body will multiply as this substance is clarified with white blood cells that can destroy viruses in the body and have more ability to form antibodies.